Engaging industry : embedding professional learning in the business curriculum. - Papadopoulos, Theo; Taylor, Tracy; Fallshaw, Eveline; Zanko, Michael (Australian Learning and Teaching Council, 2011)
This project explored and documented approaches to professional learning in the Australian higher education business curriculum. Of particular interest was the interface between universities and industry and how this has informed the development, delivery and evaluation of professional learning. The aim of this project was to investigate how to build professional learning through industry engagement in business courses in Australian universities. It did this by embedding the framework and exemplars in communities of practice within participating institutions, and beyond in the ABDC T&L Network. The outcomes are intended to further embed principles of professional learning throughout business higher education in Australia. --p.3